Returning Control to the Programmer: SIMD Intrinsics for Virtual Machines. - PARRI, JONATHAN; SHAPIRO, DANIEL; BOLIC, MIODRAG; GROZA, VOICU (Communications of the ACM, 2011)
The article discusses single instruction, multiple data (SIMD) units within interpreted software languages and the use of same to simplify computer programs. The interpreted language Java and others reportedly have failed to evolve sufficiently to properly use modern computer processors. Thus, SIMDs said to be available in most computers and servers are being underutilized as a result. Associated performance disparities that involve multicore computer processors are discussed. The authors opine regarding generic user-known parallel operation calls and their direct mapping to native SIMD calls in virtual machine internals.